Assessment of hazelnut husk as a lignocellulosic feedstock for the production of fermentable sugars and lignocellulolytic enzymes - SAYAR, AHMET ALP; KULA, CEYDA; KAZAN, DİLEK; SAYAR, NİHAT ALPAGU; PİNAR, ORKUN (SPRINGER HEIDELBERG, 2017)
The present work focuses firstly on the evaluation of the effect of laccase on enzymatic hydrolysis of hazelnut husk which is one of the most abundant lignocellulosic agricultural residues generated in Turkey. In this respect, the co-enzymatic treatment of hazelnut husk by cellulase and laccase, without a conventional pretreatment step is evaluated. Using 2.75 FPU/g substrate (40 g/L substrate) and a ratio of 131 laccase U/FPU achieved the highest reducing sugars concentration. Gas chromatography mass spectrometry confirmed that the hydrolysate was composed of glucose, xylose, mannose, arabinose and galactose. The inclusion of laccase in the enzyme mixture [carboxymethyl cellulase (CMCase) and beta-glucosidase] increased the final glucose content of the reducing sugars from 20 to 50%. Therefore, a very significant increase in glucose content of the final reducing sugars concentration was obtained by laccase addition. Furthermore, the production of cellulases and laccase by Pycnoporus sanguineus DSM 3024 using hazelnut husk as substrate was also investigated. Among the hazelnut husk concentrations tested (1.5, 6, 12, 18 g/L), the highest CMCase concentration was obtained using 12 g/L husk concentration on the 10th day of fermentation. Besides CMCase, P. sanguineus DSM 3024 produced beta-glucosidase and laccase using hazelnut husk as carbon source. In addition to CMCase and b-glucosidase, the highest laccase activity measured was 2240 +/- 98 U/L (8.89 +/- 0.39 U/mg). To the best of our knowledge, this is the first study to report hazelnut husk hydrolysis in the absence of pretreatment procedures.
Keywords: Hazelnut husk; Lignocellulose; Hydrolysis; Cellulase; Laccase; P. sanguineus; ENZYMATIC SACCHARIFICATION; PYCNOPORUS-SANGUINEUS; BIOETHANOL PRODUCTION; ETHANOL-PRODUCTION; SUNFLOWER STALKS; PRETREATMENT; HYDROLYSIS; BIOMASS; CELLULASE; LACCASE